Pemahaman Pendidik dan Tenaga Kependidikan tentang Pendidikan Umum dengan Kekhasan Agama Islam di MAN 3 Malang - Tolchah, Moch (Program Pascasarjana UIN Sunan Ampel Surabaya, 2015)
Discourses on Islamic school curriculum can be divided into theoretical and practical levels. In this paper, the practical level of the curriculum is examined in terms of its philosophical meaning within teachers, the translation of the philosophical view into school curriculum, and what strategy is being used to sharpen the curriculum messages. This article discusses the understanding of the school teachers and administrators towards the specific religious characteristics of public education at Madrasah Aliyah Negeri (MAN) 3 Malang. From the field research, this article finds three important results. First, the educators in MAN 3 Malang perceived their institution as the agent of amalgamation between Pesantren tradition and secular education to uphold excellences in academic and non-academic areas. Second, in order to materialize such philosophical thought, the educa-tors developed and implemented particular schemata. Third, in order to strengthen Islamic characteristics through curriculum development, the school applied the strategy of religious activity, direct monitoring and evaluation, educative activity designs, and implementing schoolâs vision through strategic platforms.